INTERVENTIONAL CARDIOLOGY - THE LATEST DEVELOPMENTS AND THE FUTURE - Pszczoła, Katarzyna; Cholewiński, Szymon; Ciechański, Marek; Witkowska, Edyta; Wilk, Klaudia; Kasprzyk, Aleksandra; Rejman, Piotr; Wilk, Bernadetta; Stachura, Piotr; Jurkiewicz, Katarzyna (International Journal of Innovative Technologies in Social Science, 2026)
Introduction: Cardiovascular disease (CVD) remains one of the leading causes of morbidity and mortality worldwide, accounting for a significant proportion of deaths globally.  Percutaneous coronary intervention significantly improves the treatment of obstructive coronary artery disease, reducing mortality and restenosis.This article discusses key innovations in percutaneous coronary interventions (robotics, smart implantable materials, intravascular imaging, the use of machine learning, and transcatheter electrosurgical methods) to identify their advantages, challenges, and future directions.Materials and methods: A five-year literature review analysed scientific articles on innovations in percutaneous coronary interventions, including smart materials (alloys, shape memory polymers), intravascular ultrasound, optical coherence tomography, interventional robotics, transcatheter electrosurgery, as well as the use of machine learning in diagnostics and coronary artery bifurcation stenting.Results: Smart materials (alloys, polymers) support advanced implants. Intravascular imaging increases the precision of percutaneous coronary interventions, reducing restenosis, stent thrombosis, the number of serious cardiac events and reinterventions.  Interventional robotics ensures precise stent positioning, reducing the risk of operator injury and radiation exposure. Transcatheter surgery allows for precise correction of structural defects. Machine learning optimises clinical decisions and imaging analysis, although its full application is limited by regulatory and legal issues.Conclusions: Key advances in percutaneous coronary interventions — modern implantable materials, integrated imaging, robotics, and artificial intelligence — ensure precise, safe procedures with fewer complications.